(untitled) (Research, Society and Development, 2020)
The work aims to discuss about soft palate squamous cell carcinoma, its main clinical, histological and prevalence characteristics, fundamental criteria to assist in the diagnosis and treatment of this pathology. Squamous cell carcinoma is the most common malignant tumor found in the oral cavity, affecting mainly the posterior border of the tongue, with a predilection for chronic smokers and / or alcoholics due to the greater probability of developing oral cancer associated with chronic irritating factor, its manifestation occurs in different degrees of malignancy with predominant characteristics of anaplasia, destruction of local tissue, rapid growth and capacity for metastasis. The diagnosis of squamous cell carcinoma is usually late, either due to the lack of knowledge of the pathology by the professional or even the perception of changes in the mucosa by the patient himself, who avoid seeking care for fear of the diagnosis. It is a narrative review of a qualitative and exploratory nature, which aims to list and highlight the diagnostic criteria for soft palate squamous cell carcinoma, based on clinical, histological, treatment and its etiology. An active search was performed in the following electronic databases: PUBMED, Medline, Google Scholar, Diadorim, CAPES Periodical Portal, using the Descriptors in Health Science (DeCS) and Medical Subject Headings (MeSH). To this end, the knowledge about tumor lesions is of paramount importance on the part of health professionals, thus assisting in an early diagnosis, becoming less negative and increasing patient survival rates.